2019
DOI: 10.1007/s13198-019-00912-8
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach of SWARA and fuzzy COPRAS for maintenance technicians’ selection factors ranking

Abstract: In spite of proliferation of maintenance workforce research, the maintenance community has deficient insight into the technicians' selection process. Building on studies focusing on technical crew selection and uncertainties, this paper offers a framework to potentially remedy this lack. First, the establishment of a fuzzy-rooted structure and connection of it with step-wise weight assessment ratio analysis (SWARA) and complex proportional assessment of alternatives (COPRAS) can enlarge the research community'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…A fuzzy COPRAS method uses alternatives fitness degrees to rank their ratings. This process is initiated by computing the alternatives benefit-oriented and cost-oriented values (Ighravwe & Oke, 2019). To combine an alternative's benefit-oriented criteria ratings, Equation ( 18) is considered, while Equation ( 19) is used to combine an alternative's costoriented criteria (Zavadskas et al, 1994;Zavadskas, Kaklauskas, Turskis, & Tamošaitiene, 2008).…”
Section: Copras Methodsmentioning
confidence: 99%
“…A fuzzy COPRAS method uses alternatives fitness degrees to rank their ratings. This process is initiated by computing the alternatives benefit-oriented and cost-oriented values (Ighravwe & Oke, 2019). To combine an alternative's benefit-oriented criteria ratings, Equation ( 18) is considered, while Equation ( 19) is used to combine an alternative's costoriented criteria (Zavadskas et al, 1994;Zavadskas, Kaklauskas, Turskis, & Tamošaitiene, 2008).…”
Section: Copras Methodsmentioning
confidence: 99%
“…In the study where the evaluation criteria were determined by fuzzy SWARA, the alternative selection was made with FAD. Ighravwe and Oke (2019) employed fuzzy SWARA to find the weights of maintenance activities and fuzzy CORPAS to rank the factors in a study where the selection factors of maintenance technicians in the cement manufacturing plant were evaluated. Ren et al (2019) found the criteria weights with fuzzy SWARA and alternative ranking with WASPAS in a location selection for electric vehicles in China.…”
Section: Studies On Fuzzy Swara Fuzzy Bmw Methodsmentioning
confidence: 99%
“…86,89 Recently, SWARA, a tool for evaluating and weighing criteria, is increasingly becoming the preferred method among DMs. 90,91 Experts in different areas can easily contact the general mentality of the SWARA method. 92 The most important function of this methodology is its ability to evaluate expert opinion on the accuracy of weighted criteria.…”
Section: Interval-valued Spherical Fuzzy Swaramentioning
confidence: 99%
“…The steps of the interval-valued spherical fuzzy SWARA approach can be explained as the following: 87,90,92,95,96 Step 1. Describe the alternatives to be considered in the decision-making process and the criteria used to evaluate these alternatives.…”
Section: Interval-valued Spherical Fuzzy Swaramentioning
confidence: 99%